(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article discusses changes occurring in the process of Kazakh terminology development. Due to political and economic reforms in the end of twentieth century, many areas of linguistics had been developed extensively, including terminology which is considered in this article. In history this phenomenon is called "terminological boom". Existing methods of derivation and terminology creation are supplemented with new ones. Among them lexicalsemantic method remains one of the most productive ways in formation of new words and terms. There are several ways of common lexis terminologization, their optimal and intelligent use plays significant role in terminology development. However, inadequate study of historical meanings and etymologies of words leads to some errors. Particularly today inappropriate use of borrowed words from Arabic, Persian language is an actual problem. In this article given problem is mainly considered in the process of terminologization.